Niveles de glufosinato de amonio en el control de malezas en el cultivo de banano (MusaAAA) 63p. - Rodríguez Torres, Petra Dioniocia (2012)
This research work was conducted at the Hacienda La Julia Martinique industry Noboa company, located 6 km way to Bejucal Island Parish, Canton BABA, whose coordinates are: 79 º 29 'West and 0 ° 52 'south latitude at an altitude of 60 meters. The investigation lasted for 120 days. Experimental design was used DBCA randomized block with four treatments and four replications. To determine the differences between the treatment means is used multiple range test of Tukey (P <0.05). The management of the trial was conducted according to the specifications established for the banana crop management. Raised the overall objective: To determine the efficiency of weed control herbicide glufosinate ammonium on banana plantations and specific: a) Define the level of the herbicide glufosinate ammonium, which more efficiently remove weeds in a plantation banana b) Determine the costs of treatments. Subject to the assumptions: a) the dose 2.0 L / ha-1 of the herbicide used in the study more efficiently eliminate weeds in a banana plantation and b) One of the treatments had lower costs of implementation. The best weed control was presented by treatment with doses of 2.5 L/ha-1 of herbicide Basta 150 g / L observed in this treatment a control efficiency of 95.25%, demonstrating the harmful power of glufosinate ammonium on the weeds. Best control is obtained with doses of 2.5 L/ha-1 of herbicide Basta 150 g / L, is slightly higher than the dose recommended by Bayer (2010). But even with higher concentrations of herbicide used, no toxic effects were in each of the experimental plots to which different treatments were applied in the study.